Pelatihan Pengelolaan Sampah Di Kampung Gedong Guna Peningkatan Pendapatan Masyarakat - Edi Setiawan; Zulpahmi Zulpahmi; Sumardi Sumardi (FKIP, Universitas Palangka Raya, 2024)
This community service activity was carried out with the aim of making the kampung gedong community an independent and creative community group. Through waste management into valuable products. In addition, this activity is expected to provide knowledge for the community in managing waste, so that they have alternative income. More effective waste management can also open up new business opportunities for waste pickers, such as processing organic waste into compost fertiliser or managing plastic waste into paving blocks. This activity was carried out using the lecture method when providing the material. While during the simulation, the team conducted a direct sim.